Ameryka Stanisława Barańczaka = The America of Stanisław Barańczak - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Exploring the themes of "foreignness" and "domestication" of America in the works of Stanisław Barańczak, the author of this paper attempts to provide answers to the following: what does the poet understand by "emigration" and "emigre condition"?; does the professor of Harvard University think of himself as an emigrant?; how does his "experiencing of America" look like?; how does he dismantle and deconstruct the East and Central European stereotype of the United States and the Americans?; what does the poet, a citizen of Boston (Massachusetts), truly value and view as a rescue from the sense of meaninglessness?
Keywords: Barańczak, Stanisław (1946-2014); poezja polska - 20 w.; poezja polska - 21 w.; literaturoznawstwo polskie; motywy amerykańskie